The Indianapolis automobile industry : a history, 1893-1939 - Whitaker, Sigur E. (McFarland and Company, Inc., 2018)
In 1893, Indianapolis carriage maker Charles Black created a rudimentary car--perhaps the first designed and built in America. Within 15 years, Indianapolis was a major automobile industry center rivaling Detroit, and known for quality manufacturing and innovation--the aluminum engine, disc brakes, aerodynamics, superchargers, and the rear view mirror were first developed there. When the Indianapolis Motor Speedway opened in 1909, hometown manufacturers Marmon, Stutz and Duesenberg dominated the track. The author covers their histories, along with less well known contributors to the industry, including National, American, Premier, Marion, Cole, Empire, LaFayette, Knight-Lyons and Hassler.